Average and marginal returns to upper secondary schooling in Indonesia - Pedro Carneiro; Michael Lokshin; Cristobal Ridao-Cano; Nithin Umapathi (Centre for Microdata Methods and Practice (cemmap), 2011)
This paper estimates average and marginal returns to schooling in Indonesia using a non-parametric selection model. Identification of the model is given by exogenous geographic variation in access to upper secondary schools. We find that the return to upper secondary schooling varies widely across individuals: it can be as high as 50 percent per year of schooling for those very likely to enroll in upper secondary schooling, or as low as -10 percent for those very unlikely to do so. Average returns for the student at the margin are well below those for the average student attending upper secondary schooling.
Keywords: J31; 330; Returns to Schooling; Marginal Return; Average Return; Marginal Treatment Effect; Bildungsverhalten; Bildungsertrag; Indonesien